Analysis of the family environment of children with Dandy-Walker syndrome (DWS) - Ewa Guz (Kazimierz Wielki University, 2019)
Chronic disease is a source of repetitive experiences that may permanently affect the structure and personality traits of a young patient. The whole family environment is undergoing a series of changes, which requires the support of many specialists. Dandy-Walker syndrome is such a disease as it causes many problems and often coexists with a wide range of other congenital and genetic defects. Aim. The aim of the study was to analyze and evaluate the relationship between health problems, parents' attitudes towards the problem of a sick child and parenting styles in the families of children with Dandy-Walker syndrome. Methods. 30 families from all over Poland were examined. Standardized questionnaires were applied for the research. To detect statistically significant relationships were used: chi-squared test (Chi2 test) with Yates correction, Shapiro-Wilk normality test, non-parametric Mann-Whitney U test, as well as Spearman's rank order correlation and Pearson correlation coefficient (Pearson's r). Results. In the case of analyzing the parents' approach to the problem of child's illness, the best results were obtained by the respondents in the intellectual approach, that is, this way of dealing with the child's illness dominates in their actions. Statistically significant relationships were found between the age of the fathers and the autocratic style (P = 0.01) and a wide range of statistically significant relationships between the Family Systems presented in the studied group and the emotional stages of parents. Conclusions. The results of the research on the approach to a difficult situation are as follows: emotional stages have shown that most parents are emotionally unable to cope with the child's disease, therefore parents of children born with congenital defects should be under the care of a psychological counseling center.